Association of High Dietary Acid Load With the Risk of Cancer: A Systematic Review and Meta-Analysis of Observational Studies - Keramati, Majid; Kheirouri, Sorayya; Musazadeh, Vali; Alizadeh, Mohammad (Frontiers in Nutrition, 2022)
Abstract Objective: This study aimed to determine the relationship between the high dietary acid load (DAL) and the risk of cancer. Methods: Five databases of PubMed, Web of Sciences, Scopus, Cochrane Library, and Google Scholar was searched to elicit original studies on humans, up to June 2021. Quality of the articles, risk of bias, and heterogeneity were assessed. A random-effects meta-analysis model was applied to estimate pooled effect size with a 95% confidence interval. Sensitivity analysis was performed using a fixed-effects model. Subgroup analyses were carried out based on gender, age, type of cancer, and type of DAL assessment indicator. Results: Seventeen effect sizes from 10 articles were included in the analysis. Overall, individuals with the highest DAL were associated with a 66% increased risk of cancer compared to those with the lowest DAL (p<0.001]. The risk of cancer increased 41% (p<0.001) and 53% (p=0.03) by high PRAL and NEAP, respectively. High DAL was associated with 32% (p<0.001) and 79% (p<0.001) increased risk of breast and colorectal cancers, respectively. High DAL was associated with 32% (p=0.001) and 76% (p=0.007) increased risk of cancer incident in women and men, respectively. The risk of cancer incident increased 35% (p< 0.001) and 49% (p<0.001) at age ≤ and > of 50, respectively. Conclusion: High DAL may be associated with a higher risk of cancer incidence not only in the whole studied population but also across cancer types, both genders, both DAL assessment indicators, and also among both high- and low-risk age groups for cancer.